Faktor yang Mempengaruhi Usahatani Bawang Putih di Desa Saenam Kecamatan Miomaffo Barat Kabupaten Timor Tengah Utara (Studi Kasus Kelompok Tani Cahaya Baru) - Stefanus C.M. Djoka; Simon Juan Kune (AGRIMOR, 2019)
This study aims to analize factor that affecting farming of garlic in Saenam Village on West Miomaffo District of North Central Timor. The sampling technique is done using a sampling census technique. This study was conducted in November 2017 until October 2018. The method used in the Cobb-Douglas analysis uses multiple linear regression. The results of the analysis showed the factors that affect garlic production significantly are the area of ​​land, the number of workers, experience in farming, and education. All of independent variable affect positively to farming of garlic. The other of independent variable don’t have affect significantly over to production farming of garlic.